Re-expansion pulmonary oedema - differential lung ventilation comes to the rescue - Achar, Shreepathi K (Medknow Publications & Media Pvt Ltd, 2014)
Re-expansion pulmonary oedema (REPE) is a rare complication following re-inflation of a chronically collapsed lung, which is often fatal. We present a case of a 22-year-old male who presented to the hospital with severe respiratory distress and a history of blunt abdominal trauma 3 months back. He was diagnosed to have left sided diaphragmatic hernia with a mediastinal shift to the right, and was posted for emergency repair of the same. After surgical decompression of the left hemi-thorax and reduction of the abdominal contents, re-expansion of the left lung was achieved, following which patient developed REPE. A left sided double lumen tube was then inserted to prevent flooding and cross contamination of the right lung and ventilation of both lungs was maintained intraoperatively. Post-operatively, REPE was successfully managed by differential lung ventilation with a lung salvage strategy to the left lung and a lung protective strategy to the right lung.